EVALUASI PENYEHATAN AIR BERSIH RUMAH SAKIT DENGAN PERMASALAHAN KANDUNGAN MANGAN, BESI DAN TOTAL KOLIFORM TINGGI - Fauziyah, Nada; Hermiyanti, Pratiwi; Rokhmalia, Fitri (Jurnal Higiene Sanitasi, 2022)
The quality of clean water in hospitals is an important part to pay attention to. Poor water quality can cause health problems for all hospital residents, both people with low immunity and healthy people. Clean water quality standards have been set in the Minister of Health RI no. 32 of 2017. The purpose of this study is to analyze efforts to improve the quality of clean water in public hospitals. This type of research is a literature study. The variables studied were the chemical quality of the Mn and Fe parameters, the biological quality of the total coliform parameters and the efforts to clean water. Clean water sanitation efforts in controlling Fe, Mn and microbiological parameters that can be applied to hospitals are adding chlorine to each ground tank, routine inspection of clean water microbiological parameters once a month at each sampling point that is prone to microbiological contamination in clean water. . Another effort that can be carried out is routine cleaning of each hospital reservoir in order to minimize microbiological contamination.